Biomineralization of dental tissues with natural drugs: a comprehensive review - Yuguang Liu; Ziqi Wu (Saudi Dental Journal)
Abstract This narrative review systematically examines the emerging role of natural bioactive substances in dental tissue biomineralization. Through comprehensive analysis of peer-reviewed literature (2000–2024) identified via PubMed, Web of Science, and Scopus using keywords including 'natural drugs,' 'biomineralization,' and 'dental restoration,' we evaluate three key aspects: (1) the limitations of current restorative materials (composite resins, adhesives); (2) the mechanisms of natural compounds (collagen protection, mineral deposition, demineralization inhibition); and (3) clinical translation challenges. Our analysis reveals that plant-derived flavonoids, polyphenols, and bioactive peptides show particular promise for enhancing remineralization while addressing toxicity concerns. The review concludes by proposing a research framework for developing next-generation bioactive restorative materials, highlighting knowledge gaps in long-term stability and standardized protocols.